Processing instruction : theory, research, and commentary - VanPatten, Bill (Second language acquisition research., 2004)
This work presents ten related articles that illustrate the role of processing instruction in second language acquisition. The articles provide both historical and current context, as well as describe the influence of the input processing model on PI.